Oilseeds in India with Special Reference to Arid Zone - Mann, H S; Singh, Panjab (Annals of Arid Zone, 2016)
The hectareage, production and the average productivity of major oilseeds viz. groundnut, rape and mustard, sesamum, linseed and castor in the country during the fast two decades (1955-56 to 1973-74) have been stated and future strategies suggested. Over the decades the area and production levels of 12 million ha and 5.7 million tonnes respectively in the fifties increased by 30 and 40% respectively in the seventies. The area and also the production during these decades remained highly unstable. Over these years the area and production of groundnut increased by 21 and 54% respectively while that of rape and mustard by 6.5 and 80%. In case of sesamum and linseed the increase in the production has been in proportion to the increase in the area. Contrary, inspite of 11.5% decrease in the coverage under castor in the country, the production increased by 45.5%. Average productivity of groundnut, sesamum, linseed and castor in the fifties and seventies is comparable. The increase in total oil seeds production in the country was mainly. contributed by the increase in the productivity of rape and mustard and castor seeds besides increase in the hectareage under other oilseed crops.